FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI BUAH NAGA (Studi Kasus Di Desa Tottong Kabupaten Soppeng) - H, Agus Salim; -, Yusriadi; -, Arman (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2019)
This study aims to determine the factors of production (capital, labor, Dragon Fruit prices, pesticide usage costs, land area, total production) on the income of Dragon Fruit farmers in Tottong Village, Donri-donri District, Soppeng Regency. The type of data used in this study is multiple linear regression analysis. The results of this study were then analyzed using SPSS 21 for Windows analysis tools. The variables used in this study are , namely capital, labor, Dragon Fruit prices, pesticide usage costs, land area, and total production. The results showed the variable price of Dragon Fruit and the amount of production had a significant effect on income while the variables of capital, labor, land area and costs of using pesticides had no effect on income. The results of the F test show their influence on the income of Dragon Fruit farmers. The results of the R square test show that 99.4% of the income of Dragon Fruit farmers can be explained by variables of capital, labor, Dragon Fruit prices, pesticide usage costs, land area and total production while 0.6% is influenced by other variables which are not measured in research